An Integrated Governance Framework for SME Performance and Socio-Economic Development: The Bora SME Performance System in Cambodia - Bora Khath (jfpublisher, 2026)
Small and medium-sized enterprises (SMEs) play a significant role in economic growth, employment generation, and business development, particularly in emerging economies. However, many SMEs continue to face governance, performance management, and human capital development challenges that limit long-term sustainability and competitiveness. This study proposes the Bora SME Performance System (BPS) as an integrated governance framework designed to support SME performance and organizational capability development. The framework consists of five core dimensions: Profit Engine, Process Discipline, Performance Control, People Accountability, and Potential Development. In addition, the study conceptually introduces a balanced integration between Human Resource Management (HRM) and Human Capital Management (HCM) to strengthen both operational performance and workforce capability development. Drawing on the Resource-Based View, Human Capital Theory, and contemporary governance literature, this study develops a conceptual model linking governance structures, organizational capability, and SME performance outcomes. The framework contributes to SME governance literature by offering a simplified and context-relevant model for emerging economies. The study also provides practical implications for SME leaders, consultants, and policymakers seeking to improve organizational sustainability and competitiveness. Future research is recommended to empirically validate the proposed framework across different industries and institutional contexts.